The British Empire: A Very Short Introduction - Jackson, Ashley (New York Oxford University Press, 2013)
The British Empire influenced many aspects of the world we live in today. The international system remains heavily marked by British imperialism, and the borders, nations, and federations it created. This Very Short Introduction introduces and defines the British Empire, reviewing how it evolved into such a force, and the legacy it left behind.
Includes Index and Illustrations.
Keywords: Commonwealth Countries